Adaptive control for uncertain nonlinear time-delay systems in a lower-triangular form. Issue 9 (June 2018) - Jia, Xianglei; Xu, Shengyuan; Lu, Junwei; Li, Yongmin; Chu, Yuming; Zhang, Zhengqiang
Abstract: In the presence of uncertain time-varying control coefficients, structuring parameter uncertainty and unknown state time delay, this paper proposes a continuous feedback control scheme for highly nonlinear systems without extra nonlinear growth restriction. An expansion of the backstepping method is presented based on dynamic gains and tuning functions. By Lyapunov–Krasovskii functionals, a delay-free controller is designed to regulate the original system states to zero with the other states being globally bounded.